Efficacy and Safety of Standardized Extract of Trigonella foenum‐graecum L Seeds as an Adjuvant to L‐Dopa in the Management of Patients with Parkinson's Disease. (20th March 2013) - Nathan, J.; Panjwani, Siddika; Mohan, V.; Joshi, Veena; Thakurdesai, Prasad Arvind
<x xml:space="preserve">Abstract</x> The objective of this study is to evaluate disease modifying efficacy and safety of a standardized extract of Trigonella foenum‐graecum L, Fenugreek (IBHB) (family Fabaceae) as a nutritional adjuvant to Levo‐dopa (L‐Dopa) in Parkinson's disease (PD) patients. We conducted double‐blind placebo‐controlled proof of concept clinical study of IBHB capsules (300 mg, twice daily) with matching placebo for 6 months of period in 50 patients of PD stabilized on L‐Dopa therapy. The efficacy outcome measures were the scores of Unified Parkinson's Disease Rating Scale (UPDRS ‐ total and its subsections), and Hoehn and Yahr (H&Y) staging at baseline and end of 6‐months treatment duration. Safety evaluation included haematology, biochemistry, urinalysis parameters and adverse event monitoring. Total UPDRS scores in IBHB treatment (0.098%) showed slower rise as opposed to steep rise (13.36%) shown by placebo. Further, Clinically Important Difference for total UPDRS scores and scores of motor subsection of UPDRS was found to be 5.3 and 4.8, respectively, in favour of IBHB treatment. Similar improvement was shown by IBHB in terms of H&Y staging as compared with placebo. IBHB was found to have excellent safety and tolerability profile. In conclusion, IBHB can be useful adjuvant treatment with L‐Dopa in management of PD patients. Copyright © 2013 John Wiley & Sons, Ltd.